Epígrafe de Acca Deocena en San Miguel de Bernuy (Segovia, España) - Hoces de la Guardia Bermejo, Angel Luis (Gerión. Revista de Historia Antigua, 2003)
We present a new stele of a woman with indigenous name, expressing kinship group, and decorative elements related to the death (banquet scene, trees).